Water Activity. Issue 5 (11th July 2012) - Nielsen Nielsen, O. F. O. F.; Bilde Bilde, M. M.; Frosch Frosch, M. M.
Abstract : Microorganisms require water for their metabolic activities. Only a fraction of water in foodstuffs, the so-called free water, is available for this purpose. The amounts of free water previously estimated by two different methods (Frosch et al. (2010), Frosch et al. (2011), and Low (1969)) are compared for aqueous solutions of four electrolytes, NaCl, NH4 Cl, Na2 SO4, (NH4 )2 SO4 : (i) vapour pressure measurements of the solutions relative to that of pure water (water activities) and (ii) low-wavenumber Raman spectra in the R( ν )-representation. For each electrolyte deviations were found between results from the two methods. All water molecules in the illuminated volume contribute to the Raman data. The vapor pressure measurements refer to water molecules at the water/atmosphere interface where surface tension is important. Differences in surface tension for the four electrolytes qualitatively explain deviations between the amounts of "free water" observed by the two methods.